RAGE and ICAM-1 differentially control leukocyte recruitment during acute inflammation in a stimulus-dependent manner - Frommhold, David; Kamphues, Anna; Dannenberg, Susanne; Buschmann-Prayon, Kirsten; Zablotskaya, Victoria; Tschada, Raphaela; Lange-Sperandio, Baerbel; Nawroth, Peter Paul; Pöschl, Johannes; Bierhaus, Angelika; Sperandio, Markus (BMC immunology, 2011)
The receptor for advanced glycation endproducts, RAGE, is involved in the pathogenesis of many inflammatory conditions, which is mostly related to its strong activation of NF-κB but also due to its function as ligand for the β2-integrin Mac-1. To further dissect the stimulus-dependent role of RAGE on leukocyte recruitment during inflammation, we investigated β2-integrin-dependent leukocyte adhesion in RAGE-/-and Icam1-/-mice in different cremaster muscle models of inflammation using intravital microscopy.